2015
DOI: 10.1186/s12881-015-0200-3
|View full text |Cite
|
Sign up to set email alerts
|

First de novo KCND3 mutation causes severe Kv4.3 channel dysfunction leading to early onset cerebellar ataxia, intellectual disability, oral apraxia and epilepsy

Abstract: BackgroundIdentification of the first de novo mutation in potassium voltage-gated channel, shal-related subfamily, member 3 (KCND3) in a patient with complex early onset cerebellar ataxia in order to expand the genetic and phenotypic spectrum.MethodsWhole exome sequencing in a cerebellar ataxia patient and subsequent immunocytochemistry, immunoblotting and patch clamp assays of the channel were performed.ResultsA de novo KCND3 mutation (c.877_885dupCGCGTCTTC; p.Arg293_Phe295dup) was found duplicating the RVF m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…In fact, the phenotypic spectrum of SCA19/ 22 has been widened to include a wide variety of different movement disorders, such as myoclonus, dystonia, and Parkinsonism (Duarri et al, 2012;Huin et al, 2017;Kurihara et al, 2018). Interestingly, myoclonus and dystonia were also observed in our patients carrying the novel p.C317Y and p.P375S mutations (Table 1) | 2101 Kurihara et al, 2018;Paucar et al, 2018;Smets et al, 2015). Earlier, a Japanese SCA19/22 patient with the p.T377M mutation was not reported to exhibit significant cognitive impairment (Lee et al, 2012).…”
Section: Phenotypic Heterogeneity In Sca19/22mentioning
confidence: 63%
See 2 more Smart Citations
“…In fact, the phenotypic spectrum of SCA19/ 22 has been widened to include a wide variety of different movement disorders, such as myoclonus, dystonia, and Parkinsonism (Duarri et al, 2012;Huin et al, 2017;Kurihara et al, 2018). Interestingly, myoclonus and dystonia were also observed in our patients carrying the novel p.C317Y and p.P375S mutations (Table 1) | 2101 Kurihara et al, 2018;Paucar et al, 2018;Smets et al, 2015). Earlier, a Japanese SCA19/22 patient with the p.T377M mutation was not reported to exhibit significant cognitive impairment (Lee et al, 2012).…”
Section: Phenotypic Heterogeneity In Sca19/22mentioning
confidence: 63%
“…Another intriguing issue on phenotypic heterogeneity in SCA19/22 concerns the extent of intellectual disability (Huin et al, ; Kurihara et al, ; Paucar et al, ; Smets et al, ). Earlier, a Japanese SCA19/22 patient with the p.T377M mutation was not reported to exhibit significant cognitive impairment (Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mutation of KCND3 is associated with cerebellar ataxia, intellectual disability, epilepsy, attention deficit disorders, and other clinical signs (Smets et al. ). Similar to the current findings, estrogen decreases transcriptional expression of Kv4.3 in the myometrium (Song et al.…”
Section: Discussionmentioning
confidence: 99%
“…Originally implicated for their role in epilepsy (Maljevic & Lerche, 2014; Smets et al, 2015), studies show that calcium-activated (K Ca ), voltage-dependent (K V ), and G protein-coupled inwardly-rectifying (K ir ) K + channels are targets for both acute and chronic effects of ethanol (Hopf et al, 2011; Mayfield, Blednov, & Harris, 2015; Mulholland, 2012; Mulholland, Hopf, et al, 2009). Additionally, preclinical studies have demonstrated that chronic ethanol reduces the function and trafficking of K Ca 2 ( Kcnn ), K V 4.2 ( Kcnd2 ), and K V 7.2 ( Kcnq2 ) channels in the nucleus accumbens (NAc) and hippocampus (Hopf et al, 2010; McGuier et al, 2015; Mulholland, Spencer, Hu, Kroener, & Chandler, 2015; Padula et al, 2015; Spencer, Mulholland, & Chandler, In Press), and pharmacologically enhancing K Ca 2 and K V 7 channel function attenuated voluntary drinking in rodents (Hopf et al, 2011; Knapp, O’Malley, Datta, & Ciraulo, 2014; McGuier et al, 2015; Padula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%